2015
DOI: 10.1371/journal.pone.0144744
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Bone Stress around Micro-Implants of Different Diameters and Lengths with Application of a Single or Composite Torque Force

Abstract: BackgroundStress on the bone surrounding dental micro-implants affects implant success.PurposeTo compare the stress on the bone surrounding a micro-implant after application of a single force (SF) of 200 g or a composite force (CF) of 200 g and 6 N.mm torque.Materials and MethodsFinite element models were developed for micro-implant diameters of 1.2, 1.6, and 2.0 mm, and lengths of 6, 8, 10, and 12 mm and either a SF or CF was applied. The maximum equivalent stress (Max EQS) of the bone surrounding the micro-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…The insertion torque (maximum rotations) in the same artificial bone for various lengths of OASs in the predrilled hole increased as the number of threads increased, i.e., as the length of the OAS increased. This result coincides with previous studies [ 8 , 34 , 35 , 36 , 37 , 38 ]. However, this phenomenon was not observed in the Grade 30 artificial bone ( Table 2 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The insertion torque (maximum rotations) in the same artificial bone for various lengths of OASs in the predrilled hole increased as the number of threads increased, i.e., as the length of the OAS increased. This result coincides with previous studies [ 8 , 34 , 35 , 36 , 37 , 38 ]. However, this phenomenon was not observed in the Grade 30 artificial bone ( Table 2 ).…”
Section: Discussionsupporting
confidence: 94%
“…Some similar results were observed for the manual anchorage method, i.e., during the four rotations and the maximum rotations, the insertion torque increased as the bone density increased ( p < 0.05). which coincides with previous experimental and simulative studies [ 27 , 34 , 36 , 38 , 39 ]. Furthermore, the insertion torque during the four rotations varied significantly with the OAS length, except for the Grade 40 bone.…”
Section: Discussionsupporting
confidence: 93%
“…The way in which loads are transmitted to the surrounding bone is the key factor for success or failure of the dental implant. Between different mathematical methods which can evaluate stress distribution within bone supporting dental implants, finite element analysis (FEA) is usually used in dentistry to evaluate the influence of clinical agents on the survival of implant placement, and also to predict the biomechanical status correlated with the different dental implant and alveolar bone conditions [ 5 ]. FEA allows the prediction of the stress distribution in the contact area of the implants with cortical bone, and around the apex of the implants in the surrounding bone.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mechanical stresses concentrate on the marginal bone around dental implants [ 1 ], suggesting that the maintenance of marginal bone levels for the long-term is important for successful clinical outcomes. To determine the effects of mechanical stimulation on bone around dental implants, finite element analyses have been mainly used [ 2 4 ]. Moreover, some studies have reported the effects on the jaw bone around implants using occlusal forces [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%